Amelioration genetique des bovins N'Dama. 2. Croissance des veaux avant sevrage au ranch de Madina-Diassa, Mali - Planchenault, D.; Traoré, M.T.; Roy, F.; Tall, S.H. (1986)
Calf performance in N'Dama cattle was investigated. Records on calf growth of 517 registered N'Dama calves born at Madina-Diassa station, Mali were analysed. Calf weights were evaluated at birth, 30, 90 and 205 days, the last parameter selected at weaning time. Estimates of different effects and interactions are indicated. Males had a higher significant weight than females. The batch internal effect factor and the year-season interaction were not significant, but the year-season factor was important. Medina-Diassa N'Dama strain has a small frame evidenced by calves with low birth weight (females 12 kg, males 13 kg) at breeding station management. The calves had satisfactory growth weight at 205 days with higher weight in reference to the traditional breeding system (females 59 kg, males 63 kg, vs 57 up to 60 kg respectively).